(untitled) (Eurasian Journal of Ecology, 2025)
In this study, we studied the diet of the spider Stegodyphus lineatus (Latreille, 1817) in the Zhusandal desert (Zhambyl district, Almaty region) based on the analysis of insect remains recorded in its webs. This is the first study of its kind not only for this area but also in Kazakhstan, since the diet of arachnids and their trophic relationships with other animals have not received due attention before, and this also applies to the species under consideration, S. lineatus. The information obtained has important practical significance: firstly, it is necessary for successful maintenance and breeding of this species in laboratory conditions, including for the purpose of obtaining spider venoms, peptides and other biologically active compounds; secondly, knowledge of the diet of S. lineatus allows us to assess its role as a potential regulator of insect numbers, including harmful species; thirdly, the analysis of insect remains in spider webs can be used by specialists for various purposes, such as identifying the faunal composition in a particular area, searching for specific species or groups of invertebrates occupying a similar ecological niche; Key words: arachnids, insects, fauna, diet, ecology